2018
DOI: 10.3390/su10093189
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Analysis of Green Space Network Planning for the Cooling Effect of Residential Blocks in Summer: A Case Study in Shanghai

Abstract: The effect of Urban Heat Islands (UHIs) is becoming increasingly serious in cities. Research on the adaptive planning policies for microthermal environments at the residential block level of cities is thus becoming of greater significance. Based on the cooling effect of planning control elements in residential block areas, the element effects characteristics of water bodies and vegetation distribution on the thermal environment of residential blocks were analyzed by using ENVI-met software. The simulation data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…The SVF data and spatial T values were found to be positively correlated. This result is consistent with existing research conclusions [ 34 , 50 ]. As a three-dimensional spatial factor, SVF was very important for the T value distribution of green space in our research.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The SVF data and spatial T values were found to be positively correlated. This result is consistent with existing research conclusions [ 34 , 50 ]. As a three-dimensional spatial factor, SVF was very important for the T value distribution of green space in our research.…”
Section: Resultssupporting
confidence: 94%
“…Planting smaller networks of vegetation could be a significant part of the mitigation of UHI intensity [ 33 ]. Water feature corridors have a certain influence on a certain range of downwind zones; and the different orientation of green corridors and green patches made different contributions to the cooling effect [ 34 ]. The morphological spatial pattern analysis (MSPA) mode was used to identify the main types and structure of green spaces in the landscape, which will make the foundation of the green space network [ 35 , 36 , 37 ].…”
Section: Study Area and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the rising temperatures due to climate change and the urban heat island (UHI) [3,4], it is important to recognize the role of irrigated public open space as a mitigating strategy for reducing urban heat and promoting human thermal comfort (HTC) [5,6]. In a previous study, simulation data analysis results showed that the combination of water bodies and vegetation had a synergistic cooling effect [7,8]. Public open spaces have a unique role in climate change adaptation in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…As reported earlier by Lloyd et al [9], the Australian government have devoted a great deal of human, material and financial resources to water-sensitive urban construction in recent years. Water-sensitive urban design (WSUD) is 'a thoughtful way of urban design which is to minimize the hydrological influences of urban development on the adjoining environment' [8][9][10]. Stormwater management is a part of the WSUD approach that aims at collecting stormwater to supply water sources for non-potable uses [3,10].…”
Section: Introductionmentioning
confidence: 99%